Crimes against humanity and cyberspace: Brief note on the intervention of non-state actors (De Legibus - Law Journal, 2024)
The technological development registered in the last decades and the growing utilization of cyberspace – accessible to multiple interveners, state and non-state actors – provide the rising of concerns about the perpetration of inter- national crimes through that domain. The present article aims to analyse the issue of the perpetration of crimes against humanity through cyberspace. We will exami- ne the elements of these international crimes, and observe, especially, the element concerning the policy behind the attack directed against the civilian population; within this requisite, we will consider, particularly, the situations where the policy is carried on by non-state actors. Our analysis will be based on article 7 of the Rome Statute of the International Criminal Court, pertaining to crimes against humani- ty, and the international case-law on the matter, focusing on the decision of ICC’s Pre-Trial Chamber II on the authorization of the investigation of the Situation in the Republic of Kenya. We will see that the “deterritorialization” that characterizes cyberspace and the peculiarities of some of the entities operating there stimulate the adoption of a broad interpretation of the concept of “organization” in the context of the policy element of crimes against humanity.
Keywords: crimes against humanity; cyberspace; cyberattacks; non-state actors; International Criminal Court.